Intellectual Capital Disclosure And Comprehensive Intellectual Capital Management : Evidence From Universities In Southeast Asia - Sigit Hermawan Hermawan; Duwi Rahayu; Jamaludin Jamaludin; Ruci Arizanda Rahayu; Sarwenda Biduri (Jurnal Reviu Akuntansi dan Keuangan, 2021)
The purpose of this study was to identify the practice patterns of disclosure of Intellectual Capital Disclosure by Universities in the Three Southeast Asian Countries, namely Indonesia, Malaysia, and Singapore based on the 4ICU ranking, conducting different tests of ICD practices at the University of the three countries, and providing recommendations on IC management strategies in university. This research is a type of mixed research (quantitative and qualitative). The other research results state that there are no differences in the ICD disclosure pattern between Universities in Indonesia, Malaysia, and Singapore. Recommendations for IC management strategies in higher education can be done with comprehensive intellectual capital management (CICM). The research implication is that universities in Southeast Asia need to carry out IC disclosure because it is a form of management accountability to stakeholders and also for decision making related to universities.